(untitled) (Pedagogy of Higher and Secondary Education, 2011)
Is exposed efficiency of combination of intellectual and emotionally explained development of students within the framework offered and inculcated by us to innovative conception of construction of maintenance and method of teaching of electrodynamics on consistently relativism principles with an orientation on strengthening of role of deduction, as to the method of scientific cognition, uses by a problem teaching and computer design in the process of teaching of electrodynamics in higher pedagogical educational establishment.